Evaluasi Perbedaan Kualitas Pelayanan terhadap Kepuasan Pelanggan: Studi Kasus Minimarket Waralaba dan Non-Waralaba di Kota Medan - Jan Moris Saragih; Ali Fikri Hasibuan (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
This study aims to analyze and compare the influence of Service Quality on Customer Satisfaction in two minimarkets, namely Alfamart and Daily Mart, operating in Medan City. The background of this study is based on the important role of service quality in increasing the level of customer satisfaction, especially in the modern retail sector which has a high level of competition. The approach used in this study is a descriptive quantitative method, which aims to describe and test the relationship between the variables studied systematically and measurably. The sampling technique used is purposive sampling, namely the selection of respondents based on certain criteria. The research sample consisted of 94 Alfamart customer respondents and 80 Daily Mart customer respondents, who were selected based on their experience in shopping at each minimarket. Data collection was carried out through the distribution of questionnaires containing indicators of service quality such as reliability, responsiveness, assurance, empathy, and physical evidence. The collected data were then analyzed using SPSS software version 26.0 to test the significance of the influence of Service Quality on Customer Satisfaction. The results of the analysis show that Service Quality has a positive and significant influence on Customer Satisfaction in both minimarkets. For Alfamart, the significance value was 0.008, while for Daily Mart it was 0.000, both of which are below the 0.05 threshold. This indicates a strong relationship between service quality and customer satisfaction levels. Based on the research results, it is recommended that Alfamart and Daily Mart management focus more on the service dimensions that most influence customer satisfaction. Improved service in these aspects is expected to strengthen customer loyalty and increase competitiveness amidst the intense local retail competition in Medan City.